DO WE NEED TO CARE: EMOTIONAL INTELLIGENCE AND EMPATHY OF MEDICAL AND DENTAL STUDENTS - Irfan, Muhammad; Saleem, Urooj; Sethi, Mifrah Rauf; Abdullah, Ayesha Sumera (Journal of Ayub Medical College Abbottabad, 2018)
Background: Biomedical knowledge, though pre-requisite, needs to be supported by other important skills, in order to transform medical education and healthcare delivery. This study was thus planned to analyze the correlation between emotional intelligence (EI) and empathy in medical and dental undergraduate students. Methods: This cross-sectional correlational study was conducted at public and private sector medical and dental institutions of Peshawar, Pakistan from February 2015 to June 2017. Schutte Emotional Intelligence Scale (SEiS) & Davis’ Interpersonal Reactivity Index (IRI) were used to assess emotional intelligence and empathy. The data was analyzed using SPSS-20. The p-value of <0.05 was considered significant when tests of significance were applied. Results: The mean age of the sample (n=2170) was 21.02±1.62 years. High level of EI (118.60±15.78) was reported in 1191 (54.9%) while higher empathy (63.24±14.24) was reported in 1115 (51.4%) students. Female medical students had significantly higher empathic behavior and emotional intelligence than male students (p<0.05), while no significant difference was found between male and female dental students. Medical students of private sector showed higher level of empathy as compared to public sector (p<0.05), whereas dental students of private sector showed higher level of emotional intelligence as compared to public sector (p<0.05). EI and Empathy had significant correlation (r=.370, p=0.000). Conclusion: The study showed that EI and empathy have strong correlation. Since higher levels of both have been reported in only half of the students, therefore, there is a need to work on EI of students to improve in their empathetic behavior. Keywords: Emotional Intelligence; Empathy; Medical Students; Dental Students